Improving Students' Creative Thinking Abilities and Assignment Management Through Mathematics Scaffolding Learning Strategies - Mayasari Tambunan; Lily Rohanita Hasibuan; Sakinah Ubudiyah Siregar (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2026)
Mathematics learning plays a crucial role in developing higher-order thinking skills, particularly students' creative thinking. This study aims to improve students' creative thinking and task management capabilities through the implementation of scaffolding learning strategies. The research method used was a quasi-experimental nonequivalent control group design. The research sample consisted of 60 students divided into two classes: an experimental class treated with scaffolding learning and a control class using conventional learning methods. The research instruments were a creative thinking ability test and a student task management questionnaire, which had been tested for reliability and validity. Data were analyzed using descriptive and inferential analysis. Statistical tests used included a t-test to understand the differences in results between the experimental and control classes, and an N-Gain analysis to see the increase in students' abilities. The research findings showed that students' creative thinking and task management abilities in the experimental class experienced a higher increase than in the control class. The N-Gain value of the experimental class was classified as medium to high, while the control class was classified as low to medium. Based on the research results, it can be concluded that the scaffolding learning strategy has a positive and significant effect on increasing students' creative thinking and task management abilities in mathematics learning.